INVESTİGATİON OF ZONULA OCCLUDENS-1 PROTEİN LEVEL İN RECTUM TİSSUE AFTER RADİOTHERAPY - Kurtman, Cengiz; Gümüştepe, Esra; Demirören, Serdağ; Firat , Fatma; Gökçe, Şaban Çakır; Özbilgin, Kemal (International Journal of Research -GRANTHAALAYAH, 2020)
The transmembrane protein zonula occludens of rectal tissue has function to prevents the spread of bacterial toxins into the intestinal mucosa and to systemic circulation. But radiotherapy causes ablation of crypt cell proliferation, mitotic catastrophe, and apoptosis leading to gastrointestinal mucositis. We investigated the acute radiation effect on gastrointestinal mucosa of rectum tissue thickness with immunohistochemistry method for zonula occludens-1 (ZO-1) protein in animal model. A total of 24 healthy Swiss Albino mice were divided into 4 groups, and except control group the groups of 1–3 was exposed to 500 cGy total body irradiation. All rectum tissue samples were taken from the groups of control, 24 h, 72 h, and 168 h after irradiation and stained with hematoxylin and eosin for histochemical examination, and for immunohistochemical staining with anti ZO-1 polyclonal antibody. We observed edema especially in the groups 2 and 3 but not in group 1. Immunohistochemical examination of staining of rectum tissue samples for ZO-1 showed poor staining for control group (1.48 ± 0.06) and group 1 (1.38 ± 0.09) and group 2 (1.50 ± 0.01) but the group 3 (2.12 ± 0.04) samples showed moderate ZO-1 immunostaining. It was found that the amount and thickness of ZO-1 expression increased in the late period for more than 24 hours. The comparison of the values of ZO-1 between the group 3 which is the group in the late period after radiation exposure and control group or group 1 or group 2, showed statistically significant differences (p <0.001). It was concluded that ZO-1 protein may have a role in the side effects of radiation injury, and the understanding of cellular and molecular activity will help us to develop pharmacological modulators to mitigate or treat the injury.